Pengaruh pendekatan saintifik dengan media Powerpoint terhadap hasil belajar siswa pada materi ikatan kimia - Sativa, Oryza; Jasmidi (ARKA INSTITUTE, 2022)
This study aims to: (1) To determine whether the increase in student learning outcomes taught with a scientific approach with PowerPoint media is higher than the increase in student learning outcomes taught with conventional models (2) To determine student responses to the application of a scientific approach with PowerPoint media on the subject of chemical bonds. The population of this study were all students of class X MIA SMA Swasta Amir Hamzah Medan, as many as 40 students. The sample in this study was taken using total sampling technique. The samples taken in this study were 2 classes, namely class X MIA-1 as the experimental class and X MIA-2 as the control class. Both classes were given different treatments, the experimental class with a scientific approach and PowerPoint media , while the control class was taught with a conventional model. From the posttest results, the average value of student learning outcomes in the experimental class was 88.75 and the control class was 81.50. From the N-gain results, the percentage increase in learning outcomes of the experimental class was 84.9 percent and the control class was 76.2 percent. Based on the N-gain calculation value, the increase in learning outcomes taught with a scientific approach and PowerPoint media is higher than the increase in student learning outcomes taught with conventional models. Student response to the scientific approach and PowerPoint media on chemical bonding material has a percentage of 80.25 percent and is categorized as good.